En defensa and Canícula, by Lola Blasco: revolution turned into theatre - Pilar Jódar Peinado (Feminismo/s, 2017)
En defensa… y Canícula are two works by playwright Lola Blasco that represent her political and committed theater. Coming from Feministand the theater of the revolution, and as a member of the Emergent Dramaturgy in Spain–movements from the late nineties–, her work aims to respond to historical and social conflicts, such as the 15M and the economic crisis, using metatheatrestrategies, metaphors or symbols; and, on the other hand, theatre of the self and the theater document.